Comparison of established and preliminarily proposed ASAS MRI working group cut-offs for inflammatory MRI lesions in the sacroiliac joints in radiographic and non-radiographic axial spondyloarthritis - Xenofon Baraliakos; Martin Rudwaleit; Pedro M Machado; Bengt Hoepken; Lars Bauer; Rachel Tham; Thomas Kumke; Mindy Kim (RMD Open)
Background A consensus definition for active sacroiliitis by MRI, mentioned in the Assessment of SpondyloArthritis International Society (ASAS) classification criteria for axial spondyloarthritis (axSpA), was published in 2009 and included a qualitative and quantitative MRI cut-off component. In 2021, updates to the quantitative component were preliminarily proposed. This post hoc analysis of part A of the phase 3 open-label C-OPTIMISE study (NCT02505542) explores the differences by applying the 2009 and preliminary 2021 inflammatory cut-offs on clinical outcomes of axSpA patients treated with certolizumab pegol.Methods Baseline MRI scans were used to classify 657 patients as MRI+ or MRI– according to the quantitative components of the 2009 and preliminary 2021 MRI cut-offs for inflammatory lesions. Clinical outcomes, including ASAS ≥40% improvement (ASAS40), Ankylosing Spondylitis Disease Activity Score and Bath Ankylosing Spondylitis Disease Activity Index, were reported to week 48.Results Across all analysed outcomes, 2009 MRI+ and preliminary 2021 MRI+ subgroups showed similar results. Notably, clinical outcomes for the discordant group (2009 MRI+but preliminary 2021 MRI– group; 53/657 [8.1%]) were close to those seen in MRI– patients according to either 2009 or preliminary 2021 inflammatory cut-offs, and notably different from the totality of MRI+ subgroups.Conclusion This analysis suggests that the preliminary 2021 cut-offs for MRI inflammatory lesions may slightly increase the specificity of the quantitative part of the 2009 MRI inflammatory lesion definition. The effects of the updated MRI cut-offs need to be assessed on the basis of efficacy outcomes and with the inclusion of aspects of structural changes.Trial registration number NCT02505542.